A base vem forte: A formação das jovens garotas futebolistas no Brasil em tempos de mídias sociais - Silva, Kerzia Railane Santos (2023)
The regulations introduced by CONMEBOL in 2019 can be considered one of the main reasons that boosted the development of women's football in Brazil. His targeting of football clubs was important in opening doors to aspiring athletes. In this way, we seek to answer the questions: What are the transformations that women's football has undergone in recent years? How do they interfere with career investment opportunities for new generations? How are they developing a career and how are they managing investments? The objective of this study was to investigate how young Brazilian girls are accessing training work in football clubs, taking into account the life project associated with the sport and career projection. This research is anchored in a qualitative approach in which 14 semi-structured interviews were carried out with aspiring athletes. In the case of those who are minors, a family member or responsible person was also interviewed. They are integrated into the training work at prominent football clubs on the national scene. The constructed data was analyzed using reflective thematic analysis. By results, we point out that in Brazil, the projection of the football career and its investments in the training of female football athletes is a recent phenomenon, with the update of the 2019 regulations being an important contributor to opening up this context of possibilities. However, issues such as the decentralization of the supply of training clubs are necessary, considering the prevalence in states such as São Paulo and Rio Grande do Sul. Therefore, it is imperative that sports institutions (public and private) and government bodies, as well as such as digital and television media, perform collaborative work in order to drive the continued development of the sport in the country, overcoming regional challenges, among other issues.